Design of a ratiometric two-photon fluorescent probe for dual-response of mitochondrial SO2 derivatives and viscosity in cells and in vivo. (December 2019) - Sun, Chuan; Cao, Wangfei; Zhang, Wan; Zhang, Lanlan; Feng, Yan; Fang, Min; Xu, Guoyong; Shao, Zonglong; Yang, Xiuli; Meng, Xiangming
Abstract: The content of sulfur dioxide (SO2 ) in mitochondria is related to various physiological and pathological processes. The irregular viscosity in mitochondria would result in mitochondria disorders. In this research, a novel ratiometric two-photon fluorescent probe (MBCB ) based on carbazole framework has been strategically designed and synthesized for dual-detection of mitochondrial SO2 derivatives and viscosity. The results show that probeMBCB is capable of responding to SO2 derivatives and viscosity using dual-color imaging.MBCB can not only recognize SO2 derivatives utilizing a ratiometric change of fluorescent intensity ( I 434 nm / I 600 nm ), but also shows a high sensitivity and selectivity for monitoring SO2 . On the other hand, the fluorescent intensity ratio ( I 567 nm / I 415 nm ) ofMBCB increased with the increment of viscosity and exhibited a good logarithmic linear relationship between the ratio and viscosity (R 2 = 0.99). Satisfactorily, probeMBCB has a good targeting ability to mitochondria and a low cell cytotoxicity, and can be successfully applied to detect HSO3 − in living cells and in vivo . Furthermore, the probe can visualize the change of mitochondrial viscosity induced by nystatin. Graphical abstract: A dual-response ratiometric two-photon fluorescent probe (MBCB ) for monitoring mitochondrial SO2 derivatives and viscosity has been developed.Image 1 Highlights: A two-photon fluorescent probe for dual-detection of SO2 derivatives and viscosity was designed. Probe is capable of responding to SO2 derivatives and viscosity using dual-color imaging. Probe has a good targeting ability to mitochondria and a low cell cytotoxicity. Probe can be applied for bio-imaging of SO2 derivatives in vitro and in vivo. Probe can visualize the change of mitochondrial viscosity induced by nystatin.